Development of Interactive Learning Media Using ClassPoint to Enhance Students’ Critical Thinking Skills in Fluid Mechanics - Laely Nurul Fitriah; Bodi Gunawan; Desy Hanisa Putri (FKIP - Universitas Riau, 2026)
This study was motivated by students’ low critical thinking skills in physics learning, particularly in fluid mechanics, as well as the continued implementation of teacher-centered instruction in classrooms. The purpose of this study was to develop interactive learning media assisted by ClassPoint to improve students’ critical thinking skills in fluid mechanics. This study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The implementation phase applied a one-group pretest-posttest design involving 29 eleventh-grade students at a public senior high school in Bengkulu City. Data were collected through interviews, questionnaires, expert validation sheets, and pretest-posttest tests. The results showed that the developed media achieved high validity in terms of content, presentation, and media appropriateness based on expert evaluations. The implementation of the media also improved students’ critical thinking skills and encouraged active participation during learning activities. In addition, students gave very positive responses toward the use of the media in physics learning. Therefore, the interactive learning media assisted by ClassPoint are considered feasible and effective for supporting physics learning and improving students’ critical thinking skills in fluid mechanics.